Growth performance and genetic diversity in four strains of Asian sea bass, Lates calcarifer (Bloch, 1790) cultivated in Thailand - Joerakate, Weerakit; Yenmak, Suthajaree; Senanan, Wansuk; Tunkijjanukij, Suriyan; Koonawootrittriron, Skorn; Poompuang, Supawadee (Agriculture and Natural Resources, 2018)
The growth and genetic variation were examined of four strains of Asian sea bass: Chon Buri (CHB), Chumphon (CHP), Chachoengsao (CHS), and Samut Songkhram (SMS). The growth of juvenile fish (90 d post-hatch) was assessed in earthen-pond culture environments for 220 d. Fish, with an average initial weight ±SE ranging from 9.48 ± 0.12 to 9.74 ± 0.16 g, depending on strain, were stocked in four 6 m x 6 m x 1.2 m stationary cages (replicates) in each of four 800 m2 ponds at 3 fish per m3 following a randomized complete block design. Strain differences in body weight were highly significant (p < 0.001). The CHS strain displayed the highest final mean weight ± SE (730.23 ± 10.48 g) followed by CHP (709.60 ± 14.76 g), CHB (661.66 ± 14.92 g) and SMS (650.60 ± 11.66 g). The absolute growth rates were significantly different among strains, with values ranging from 2.86 to 3.22 g/d for SMS and CHS. Similarly, specific growth rates differed significantly among strains and ranged from 1.88 to 1.97% for SMS and CHS. All four strains had moderate to high levels of microsatellite genetic variation, with average numbers of alleles per locus ranging from 6.8 to 9.4, effective numbers of alleles per locus ranging from 4.33 to 5.99 and observed heterozygosities ranging from 0.75 to 0.81. Overall, the CHS strain, which exhibited the highest numbers of alleles and an effective population size of 55, was the best performing strain.